Power Rangers, Dinothunder. Volume 1, Day of the dino - Hoffmeier, Mark.; Sloan, Douglas; Napier, James, 1982-; Duhaney, Kevin; Lahana, Emma, 1984-; Frank, Jason David, 1973-; Parazzo, Jeffrey; Gaines, Latham; Smith, Miriama; Devine, Katrina, 1980-; Hern, Tom, 1984-; Lynch, Bruce; et al. (Burbank, CA : Buena Vista Home Entertainment, 2004)
When an evil paleontologist unleases his Dino Zords - creatures of incredible strength and intelligence - the Black Power Ranger must reignite his secret past to stop him. He recruits three students as likely new Rangers, but can a rebellious soccer star, a loner musician and a laid- back champion gamer become superheroes in time to save the world from these powerful mutant terrors?
Day of the dino, part I -- Day of the dino, part II -- Wave goodbye -- Lagacy of power -- Back in black -- A storm before the calm, part I -- A storm before the calm, part II.
Originally released as part of a television series in 2003.
Special features: Ninja moves; virtual DinoThunder trading cards.
Music, Bruce Lynch.
James Napier, Kevin Duhaney, Emma Lahana, Jason David Frank, Jeffrey Parazzo, Latham Gaines, Miriama Smith, Katrina Devine, Tom Hern.
Not rated.
DVD, Region 1, full screen (1.33:1) presentation; Dolby Digital surround.
Keywords: Crime prevention -- Juvenile drama; Paleontologists -- Juvenile drama; Dinosaurs -- Juvenile drama; Action and adventure television programs -- Japan; Children's television programs -- Japan; Video recordings for the hearing impaired